1995
DOI: 10.1093/schbul/21.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and Motives for Substance Use in Schizophrenia

Abstract: This study examined the internal reliability of standardized measures of substance use expectancies and motives in a schizophrenia population (n = 70) and the relationship of these expectancies and motives to alcohol and drug use disorders. Internal reliabilities were uniformly high for the subscales of the expectancy and motive measures. Analyses of the relationship between substance use disorders and expectancies revealed strong substance-specific expectations. Alcohol expectancies were related to alcohol di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 32 publications
8
58
1
Order By: Relevance
“…Like Spencer et al [31] , Mueser et al [27] also used the DMM [43] , but an earlier version. Mueser et al [27] adapted the DMM for assessing motives for drug use and developed the Drug Use Motives Measure.…”
Section: Reasons For Substance Use With Cannabis As One Of the Main Smentioning
confidence: 99%
See 3 more Smart Citations
“…Like Spencer et al [31] , Mueser et al [27] also used the DMM [43] , but an earlier version. Mueser et al [27] adapted the DMM for assessing motives for drug use and developed the Drug Use Motives Measure.…”
Section: Reasons For Substance Use With Cannabis As One Of the Main Smentioning
confidence: 99%
“…Like Spencer et al [31] , Mueser et al [27] also used the DMM [43] , but an earlier version. Mueser et al [27] adapted the DMM for assessing motives for drug use and developed the Drug Use Motives Measure. Mueser et al [27] scores were reported separately for different groups of drug-abusing patients, ranging from groups with no abuse to recent drug abuse.…”
Section: Reasons For Substance Use With Cannabis As One Of the Main Smentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with psychosis like schizophrenia and/or bipolar disorder, substance abuse has been reported [1][2][3][4]. Previous studies have found high prevalence of schizophrenia and other psychotic disorders among users of illicit substances like cannabis [5] and amphetamines [6,7].…”
Section: Introductionmentioning
confidence: 99%